Efektivitas Program Upskilling dan Reskilling bagi Peningkatan Kompetensi Guru SMK di Kota Medan - Maslina Siagian (UMSU, 2023)
The purpose of this study was to determine and analyze the effectiveness of upskilling and reskilling programs and the professional competence of vocational teachers before and after attending upskilling and reskilling training in Kota Medan. This research uses a combination approach (mix method), with a sequential exploratory. The study began by collecting qualitative data and continued with quantitative research on the professional competence of vocational school teachers before and after attending upskilling and reskilling training using a questionnaire. The research was carried out at SMK Negeri 2 Medan, SMK Negeri 7 Medan, SMK Negeri 9 Medan, SMK Swasta Dwi Warna and SMK Swasta Taman Siswa Medan. Primary data sources come from the results of interviews and questionnaires to 20 teachers who have attended upskilling and reskilling training. The findings of the study showed that the upskilling and reskilling program for increasing the professional competence of vocational teachers in Kota Medan was effective, and from the results of the questionnaire it was seen that there was an increase in the professional competence of vocational teachers after attending this training where the average data of teacher professional competence before attending upskilling and reskilling training is 45.30 and the average professional competence of teachers after attending the upskilling and reskilling training is 49.95, with an average increase in teacher professional competence of 4.65, the results of the paired sample test correlations about the relationship (correlation) between the data before attending the upskilling and reskilling training and the data after attending the upskilling and reskilling training obtained a correlation value of 0.909, the results of the paired sample test obtained a data significance value of 0.000 0.005 which means that there is a significant difference between the professional competence of teachers before attending the training and after attending the training. upskilling and reskilling training.